Judi Online di Kalangan Pelajar Studi Kasus di SMK PGRI Sooko Mojokerto - Rakhmat Nur Amanulloh; M. Syarif; Syaikhu Rozi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The phenomenon of online gambling among students has become a serious concern in today's digital era. Although religious education has been taught in schools, the reality is that many students do not fully understand the negative impact of online gambling practices. Previous studies have focused more on students or adolescents in general, without highlighting the role of Islamic Religious Education (PAI) teachers in shaping student understanding at the Vocational High School (SMK) level. This is a research gap that needs to be bridged through more contextual and applicative studies. This study aims to reveal the extent of students' understanding of online gambling and analyze the strategies used by PAI teachers in strengthening awareness of the dangers of this behavior. The approach used is descriptive qualitative with a case study design, located at SMK PGRI Sooko Mojokerto. Data collection techniques include observation, in-depth interviews, and documentation, which are then analyzed using interactive models from Miles, Huberman, and Saldaña. The results show that students' understanding of online gambling is mostly obtained from social media and the friendly environment, with an initial understanding that tends to be permissive. However, after experiencing direct negative impacts, such as impaired learning focus, decreased motivation, and moral guilt, students' attitudes began to change towards rejection. On the other hand, PAI teachers apply educational strategies through contextual lectures, open dialogue, visualization of case studies, and spiritual strengthening through routine religious activities. This strategy is not only preventive, but also touches the emotional and spiritual aspects of students comprehensively. This study recommends strengthening collaboration between schools, parents, and external parties such as religious institutions and law enforcement in an effort to prevent online gambling practices. In addition, it is necessary to develop a PAI learning model that is more responsive to today's digital issues. The limitations of this study lie in the scope of a single location, so further research is recommended to involve more schools to expand the generalization of the findings.